Wacana Rasisme Terhadap Golongan Minoritas di Jepang (Tinjauan Analisis Wacana Kritis) - Luhur Wedayanti, Ni Putu; Andry Anita Dewi, Ni Made (International Seminar on Austronesian Languages and Literature, 2021)
Othering phenomenon, recently became a common reality that happened widely. People are tend to feel at ease when interact within their community that has similar vision in life, preferences, or else. However, most of those people often think and act as their communities or societies are better than the other. So, on purposely they will produce utterances or acts abruptly which could trigger anxiety for people whom become their hatred object. On the other hand, a rapid development on technology of information change people attitudes while communicate online. People can interact without any obligation to disclose their identity on the internet. They could post anything online that may read by anyone without any thought or symphaty for the victim.  This article try to analyze whether on the text that found online contain racism with Fairclough’s critical discourse analysis. With three dimension of analysis from textual level, discourse level and sosioculture point of view